Twee sedentaire Polychaeten uit he brakke water var Nederland - Horst, R. (Zoologische Mededeelingen (Leiden), 1919)
No abstract. Describes a polychaete from the Alkmaar received from Dr Romijn, "who is busy with an investigation of the Oligochaetidae of the waterways in the Netherlands"
World Polychaeta Database (WPolyDb)